Note that if you upsample a sequence $x[n]$ by a factor $M$ you have
$$y[Mn]=x[n]\tag{1}$$
The DFT of $x[n]$ is
$$X[k]=\sum_{n=0}^{N-1}x[n]e^{-j\frac{2\pi}{N}nk}\tag{2}$$
The DFT length of $y[n]$ is $MN$, so the DFT of $y[n]$ is
$$Y[k]=\sum_{n=0}^{MN-1}y[n]e^{-j\frac{2\pi}{MN}nk}\tag{3}$$
Since only every $M^{th}$ sample of $y[n]$ is non-zero, $(3)$ can be written as
$$Y[k]=\sum_{n=0}^{N-1}y[Mn]e^{-j\frac{2\pi}{MN}Mnk}=\sum_{n=0}^{N-1}y[Mn]e^{-j\frac{2\pi}{N}nk}\tag{4}$$
With $(1)$ we get
$$Y[k]=X[k]\tag{5}$$
Note that from $(2)$ $X[k]$ is $N$-periodic, so the length $MN$ DFT of $y[n]$ is just an $M$-fold repetition of the DFT coefficients of $x[n]$.
A simple example:
x = [1,1];
X = fft(x)
ans =
2 0
y = [1,0,1,0];
fft(y)
ans =
2 0 2 0
y=[1,0,0,1,0,0];
fft(y)
ans =
2 0 2 0 2 0